Tennessee Criteria of Excellence in Reading - Tennessee State Dept. of Education, Nashville; Tennessee State Dept. of Education, Nashville ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The criteria of excellence outlined in this book have been organized according to the following five components, identified as essential for effective reading programs: school and community commitment, staff and staff development, the learning environment, program development and implementation, and instructional materials. For each of the components, a rating scale and a list of criteria are provided. An appendix contains both sample worksheets and summary sheets for a profile chart, the strengths of the program, the areas in need of improvement, and the priorities. (JM)
Educational level discussed: Adult Basic Education.
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Educational Environment; Elementary Secondary Education; Evaluation Criteria; Instructional Materials; Program Development; Reading Instruction; Reading Programs; School Community Relationship; State Programs; Teachers; Right to Read; Tennessee; Reports, Descriptive